2020
DOI: 10.3390/jcm9040900
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Default Mode Network Activation During Delay Discounting in Adolescents with Anorexia Nervosa After Partial Weight Restoration: A Longitudinal fMRI Study

Abstract: The capacity of patients with anorexia nervosa (AN) to resist food-based rewards is often assumed to reflect excessive self-control. Previous cross-sectional functional magnetic resonance imaging (fMRI) studies utilizing the delay discounting (DD) paradigm, an index of impulsivity and self-control, suggested altered neural efficiency of decision-making in acutely underweight patients (acAN) and a relative normalization in long-term, weight-recovered individuals with a history of AN (recAN). The current longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 82 publications
3
11
1
Order By: Relevance
“…We find an almost complete normalization of all rsfMRI alterations after refeeding therapy. These findings are in line with results of Cha et al (2016) and are further supported by similar conclusions from longitudinal task-based fMRI (Decker et al, 2015;Doose et al, 2020) as well as structural (brain gyrification) studies (Bernardoni et al, 2018). Moreover, the lack of differences between long-time recovered AN and HC in our study further supports the notion that the here identified sizeable rsfMRI alterations may constitute temporal, presumably starvation-related, state effects of the disorder.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We find an almost complete normalization of all rsfMRI alterations after refeeding therapy. These findings are in line with results of Cha et al (2016) and are further supported by similar conclusions from longitudinal task-based fMRI (Decker et al, 2015;Doose et al, 2020) as well as structural (brain gyrification) studies (Bernardoni et al, 2018). Moreover, the lack of differences between long-time recovered AN and HC in our study further supports the notion that the here identified sizeable rsfMRI alterations may constitute temporal, presumably starvation-related, state effects of the disorder.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with results of Cha et al 14 and are further supported by similar conclusions from longitudinal task-based fMRI studies. 44,45 This lack of differences between long-time recovered AN and HC in our study further supports the notion that the identified rsfMRI alterations may constitute temporal, presumably starvation-related, state effects of the disorder. Differences to previous research indicating persistent alterations in varying brain networks in short- 15 and long-term recovered AN 1619 may be due to the longer average recovery time (5.3 ± 3 years) and the considerably shorter illness durations in our cohorts (tables S20, S21).…”
Section: Discussionsupporting
confidence: 85%
“…Another study, 46 using a slightly different delay-discounting task and with a younger population of AN, found no delay discounting differences between individuals with AN and HC and no group differences in the striatum, but did find group differences in the dorsal ACC, which were correlated with reward valuation. In two separate studies, there were no behavioral or neural differences between weight-restored AN and HC 47,48 . In a study comparing the effects of metabolic state on delay discounting in individuals who had remitted from AN compared with HCs, there were no group differences in task performance; the AN group did not show fed-versus-fasted neural differences and the HC group did.…”
Section: Reward Processingmentioning
confidence: 84%
“…AcAN participants were admitted to a specialized eating disorder program of the University Hospital Carl Gustav Carus at the TU Dresden and were assessed within 96 h after the initiation of intensive treatment (acAN-T1, study timepoint T1). Forty-seven of the 77 acAN patients were reassessed after partial/short-term weight rehabilitation (acAN-T2, study timepoint T2) with a BMI increase of at least 10% as in previous longitudinal studies from our group [ 55 , 56 ]. In the current sample, all acAN had a ≥13% BMI increase at follow-up.…”
Section: Methodsmentioning
confidence: 99%